Neural Tube Defects, Patho-physiology and Relationship of Serum Zinc Level: A Review - Dey, Arjun Chandra; Mannan, Mohammad Abdul; Saha, Laxmi; Noor, Khaled; Shahidullah, Mohammad (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v33i3.5691 Bangladesh Journal of Child Health 2009; Vol.33(3): 104-110